O framework JavaServer Faces - Welzel, Jonathan Nascimento (2011)
In order to supply the growing demand for this kind of application the right development tools must be used, and for that purpose the JavaServer Faces (JSF) framework was created. JSF is designed to significantly ease the burden of writing and maintaining applications of this nature by offering a simple approach to user interface (UI) design and integration between business logic. This paper depicts the main features and benefits offered by JSF as well as gives a detailed overview of its present and previous version specifically approaching the differences between them. By the end, these differences will be shown using code snippets that intend to demonstrate how they can help to speed up the development process.